Chemical composition and biological activity of the essential oil from the root of Jatropha pelargoniifolia Courb. native to Saudi Arabia - Hanan Aati; Ali El-Gamal; Oliver Kayser (Elsevier, 2019)
The chemical composition of the essential oil from Jatropha pelargoniifolia roots was determined via GC-FID. There were 80 compounds, representing 99.99% of the total oil constituents. Among these, 77.31% were sesquiterpenes, 14.62% were fatty acids, 7.21% were other components (i.e., phenolics, hydrocarbons, etc.), and 0.85% were monoterpenes. The major compounds in the oil were γ-eudesmol (35.31%), 5-guaien-11-ol (14.43%), epi-cedrol (8.19%), oleic acid (5.23%), bulnesol (4.45%), α-linoleic acid (4.20%), 3,4-dimethoxycinnamic acid (3.83%), palmitic acid (2.69%), isolongifolanone (2.68%), eicosane (1.41%), and cedrol (1.14%). Oxygenated sesquiterpenes were found to represent more than 50% percent of the total oil content. Moreover, the essential oil was evaluated for anti-inflammatory, antioxidant, antipyretic, and antinociceptive activities using in vivo and in vitro models. Additionally, the antioxidant potential of the oil was evaluated using various in vitro antioxidant tests, including DPPH·, ABTS·+ and FRAP. At a dose of 240 µl/kg, the oil showed anti-inflammatory (59.12%), antipyretic (37.00 ± 0.11), and antinociceptive (47.58%) activities and showed significant (p < 0.001) effect as compared to a standard drug (phenylbutazone and indomethacin). These findings demonstrated that the essential oil of Jatropha pelargoniifolia root could be used as a natural source for their anti-inflammatory, antinociceptive, antipyretic, and antioxidant effects. Keywords: Jatropha pelargoniifolia, Euphorbiaceae, Antinociceptive activity, Anti-inflammatory activity, Antipyretic activity, Antioxidant activity, Essential oil